Back Cover: Efficient Qubit Routing for a Globally Connected Trapped Ion Quantum Computer (Adv. Quantum Technol. 8/2020). Issue 8 (4th August 2020) - Webber, Mark; Herbert, Steven; Weidt, Sebastian; Hensinger, Winfried K.
Abstract : The cost of enabling connectivity in noisy intermediate‐scale quantum (NISQ) devices is an important factor in determining computational power. A particular architecture for trapped‐ion quantum computing relies on shuttling ions. An efficient ion routing algorithm has been created along with an appropriate error model, which can be used to estimate the achievable circuit depth and quantum volume as a function of experimental parameters. For further details see article number 2000027 by Winfried K. Hensinger and co‐workers.